Randomized, Controlled Pilot Study of Low-Dose Human Chorionic Gonadotropin Administration Beginning From the Early Follicular Phase for Women With Polycystic Ovarian Syndrome Undergoing Ovarian Stimulation Using the Progesterone Protocol - Zhu, Xiuxian; Fu, Yonglun (Frontiers in Endocrinology, 2019)
Purpose: To illustrate whether low-dose human chorionic gonadotropin (hCG) administration during the early follicular phase could reduce the number of large preovulatory follicles in women with polycystic ovarian syndrome (PCOS) undergoing ovarian stimulation using the progesterone protocol. Methods: We performed a randomized, controlled pilot trial at a university-affiliated tertiary hospital. A total of 40 infertile women undergoing their first in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) treatment with the freeze-all strategy were included. Human menopausal gonadotropin (hMG) and progesterone soft capsule 100 mg/d were added simultaneously beginning from menstrual cycle day 3 for all participants. Low-dose hCG (200 IU) was injected every 3 days in the study group from the first day of ovarian stimulation until trigger. The primary outcome was the number of large preovulatory follicles. Secondary outcomes included the incidence of ovarian hyperstimulation syndrome (OHSS); the number of oocytes retrieved, mature oocytes, and good-quality embryos; and clinical results after frozen-thawed embryo transfer (FET) cycles. Results: The study group had slightly more large preovulatory follicles than the control group (17.75 ± 10 vs. 13.2 ± 5.34; P > 0.05). None of the participants experienced severe OHSS. There were no statistically significant differences in the number of oocytes retrieved (15.9 ± 8.46 vs. 15.75 ± 6.96), mature oocytes (13.55 ± 6.56 vs. 13.4 ± 6.34), and good-quality embryos (5.5 ± 3.41 vs. 4.9 ± 2.99) between the two groups (P > 0.05). Clinical pregnancy rates (65.52 vs. 41.94%; P = 0.067) and live birth rates (48.28 vs. 35.48%; P = 0.315) per transfer following FET of the study group were higher than those of the control group, but without statistical significance. Conclusions: Administration of low-dose hCG from the early follicular phase for PCOS patients undergoing ovarian stimulation with progesterone protocol may lead to slightly more early preovulatory follicles and marginally, but not significantly, higher clinical pregnancy rates. A continuous trial should be performed to explore the effects of supplementation with different doses of hCG from the start of ovarian stimulation in PCOS patients using the progesterone protocol. Clinical Trial Registration:Chictr.org.cn, identifier: ChiCTR-IOR-15007165